Ethical Dilemma in Patients Selection during COVID-19 Pandemic in Indonesia: Choosing Who Shall Live or Die - Urfa Khairatun Hisan (Journal of Health Sciences and Medical Development, 2023)
Debates surrounding the patient selection criteria for medical resources rationing have been sparked since decades ago. The arrival of COVID-19 has, once again, raised this debate. Due to its abrupt arrival, rapid infection rate, and unknown pathophysiology, COVID-19 has overwhelmed everyone, including healthcare stakeholders, causing a shortage of medical resources (e.g., beds, ventilators, oxygen supplies, drugs and medicines, and even personal protective equipment). Subsequently, resource rationing through patient selection is inevitable. This article comprehensively summarized the ethical dilemmas in patient selection during the COVID-19 pandemic, especially in Indonesia. We divide the dilemma into two major groups: the elderly and important people. We also present a scientific discussion covering the patients' selection approaches (first-come-first-served (FCFS)-based, severity-based, age-based, time-division/future prediction, equality-based, and random rationing). We reveal that there is no perfectly ideal approach for patient selection without sacrificing any factors. Since decades ago, patient selection policy has placed the elderly groups in an unfavorable position. The COVID-19 pandemic has, once more, showing us that elderly groups are still given lower priorities in the scarce medical resource setting. Lastly, until we are able to provide sufficient healthcare resources, this condition might be, and will always be, a bitter pill to swallow.